The Evolution of Acculturation and Development Models for Understanding Immigrant Children and Youth Adjustment. (18th October 2019) - Juang, Linda P.; Syed, Moin
Abstract: Acculturation and developmental theories and frameworks have merged steadily to portray the development and adaptation of immigrant children more comprehensively. In this article, we trace this evolution to show how research has increasingly provided greater specificity in identifying the domains, dimensions, and contexts of acculturation processes, as integrated with greater concern for developmental principles. Although models have become more complex and comprehensive, we still need well‐formulated theoretical explanations for the many processes that link development with acculturation and subsequent adjustment. We argue that novel developmental and acculturation concepts could advance specific lines of research situated in these complex models. By continuing to integrate developmental science and acculturation research more explicitly, we can arrive at a clearer and more complete understanding of how immigrant children and youth adapt across the lifespan.